Upaya Pemerintah Indonesia dalam Menurunkan Angka Peredaran Narkotika di Indonesia yang Dilakukan oleh Pengedar Asing Tahun 2014-2016 - Nabiela Ramadhani; Nadia Farabi (Journal of International Relations Diponegoro, 2019)
Drug trafficking has becoming one of the major crimes and threatening the Indonesian’s national security at the same time. Every single year, drug trafficking’s cases are increasing rapidly throughout the nation. Nevertheless, drug trafficking within the local market keep ascending from times to times, the growth of drug trafficking’s cases by foreign part is having a downside from 2014 – 2016. Going through the fact that as a nation, Indonesia is still facing the drug trafficking issue which spread swiftly then the Indonesian Government urge to take a bigger action to exterminate this problem in to the very root. By using the descriptive method as the research method for this research, there is the thoroughly explanation about how the Indonesian Government taking a direct action in order to suppressing the drug trafficking number in Indonesia. The National Security concept is used to answer the research question. The result presents the fact that Indonesian Government’s effort to holding down the drug trafficking case in Indonesia is by increasing the national security which one of the implementations is by intensifying the resilience in the border region